Microfibra de cáscara de banano y harina de pulpa de camote (Ipomoea batatas L. lam) en la calidad final de una galleta - Moreira Anchundia, Ángela Inés (2021)
The objective of this study was to evaluate the effect of different percentages of banana microfiber and Guayaco Morado sweet potato flour on the nutritional, microbiological and sensory quality of a cookie. To obtain it, different percentages of flours were used (10/90, 20/80, 30/70%), which were obtained through a mechanical process. Subsequently, 6 treatments were evaluated with 3 replicates in one design (DCA), using the Shapiro-Wilk and Levene test, showing that the humidity presented statistical difference, therefore, a demonstration was made through a study considered as "Tukey" at 5 % in different factors such as: total carbohydrates, cholesterol, sugars, fat, fiber, sodium, which were evaluated by non-parametric Kruskal-Wallis tests, while the percentage of cholesterol was the only one that did not influence between the dosages of banana peel microfiber and Guayaco Morado sweet potato flour in all treatments, however, for the other variables the content of both flours influences their nutritional composition. The microbiological analyzes determined parameters such as: mesophilic aerobes of 1,0 x 103, molds and yeasts with 1,0 x 102, carried out at each treatment, which are within the ranges allowed by the INEN 2085: 2005 standard. Finally, an affective test was carried out by preference to the 3 best treatments according to the highest protein percentage, through the Friedman test it was evidenced that T6 (1,667) was the most preferred by untrained tasters, in comparison to T4 (2,181) and T5 (2,153).